Platinum-Group Minerals in Chromitites of the Niquelandia Layered Intrusion (Central Goias, Brazil): Their Magmatic Origin and Low-Temperature Reworking during Serpentinization and Lateritic Weathering - Garuti, Giorgio; Zaccarini, Federica; Proenza, Joaquin A.; Thalhammer, Oskar A. R.; Angeli, Nelson [UNESP] (Mdpi Ag, 2012)
A variety of platinum-group-minerals (PGM) have been found to occur associated with the chromitite and dunite layers in the Niquelandia igneous complex. Two genetically distinct populations of PGM have been identified corresponding to phases crystallized at high temperatures (primary), and others formed or modified during post-magmatic serpentinization and lateritic weathering (secondary). Primary PGM have been found in moderately serpentinized chromitite and dunite, usually included in fresh chromite grains or partially oxidized interstitial sulfides. Due to topographically controlled lateritic weathering, the silicate rocks are totally transformed to a smectite-kaolinite-garnierite-amorphous silica assemblage, while the chromite is changed into a massive aggregate of a spinel phase having low-Mg and a low Fe3+/Fe2+ ratio, intimately associated with Ti-minerals, amorphous Fe-hydroxides, goethite, hematite and magnetite. The PGM in part survive alteration, and in part are corroded as a result of deep chemical weathering. Laurite is altered to Ru-oxides or re-crystallizes together with secondary Mg-ilmenite. Other PGM, especially the Pt-Fe alloys, re-precipitate within the altered chromite together with kaolinite and Fe-hydroxides. Textural evidence suggests that re-deposition of secondary PGM took place during chromite alteration, controlled by variation of the redox conditions on a microscopic scale.
Keywords: Chromitite; PGM; laterite; weathering; Niquelandia